New method for self-heating estimation using only DC measurements - Mori, C. A. B.; Agopian, P. G. D. [UNESP]; Martino, J. A.; Gamiz, F.; Sverdlov, V; Sampedro, C.; Donetti, L. (Ieee, 2018)
This paper reports a new method for estimating the thermal resistance of a device using the inverse of the transistor efficiency as a function of the power applied to the transistor's channel. The advantages of this new method are the use of DC measurements only and errors smaller than 4% in the estimation of the channel temperature increase due to the SHE when compared to a pulsed method for the UTBB SOI studied in this work.
Keywords: Self-heating effect; Silicon-On-Insulator; UTBB